A Igreja Assembleia de Deus e as práticas de lazer: territorialidades nas comunidades do município de Bragança (PA) - Roscoche, Luiz Fernando (2018)
This work aims to verify how the conversion to the Assembly of God Church has changed the leisure territorialities of the faithful in the communities of the city of Bragança, located in the northeastern region of the state of Pará, in the Brazilian Amazon. This research starts from a perspective based on human geography, an approach to cultural geography. Considering religion and leisure from the theory of liquidity modernity sought to understand the material and immaterial territoriality of the subjects. The approach proposed in the thesis is a qualitative research, using primary and secondary sources, historical documents and in particular questionnaires, interviews and field observations. In order to better understand the problem, exploratory field research was carried out by observing and conducting conversations and interviews in communities in the municipality, where faithful and members of the church were researched. The research was divided in two moments, the first of characterization of the profile of the faithful and their religious and leisure territorialities, electing those who opted voluntarily for participating in the research. In the second stage, in-depth qualitative interviews were conducted with some faithful volunteers, either in individual interview or in focus groups. The interviews, testimonies and transcription of cults and events were analyzed through content analysis and discourse. For the purposes of this research, the subjects were divided into central subjects, that is, converts to the Assembly of God Church, as well as members of the church as pastors, presbyters, workers) and the contextual subjects who, although born in the evangelical faith, help to contextualize the converted evangelical. It is possible to verify that religious change creates new religious and leisure territoriality, even though they resist elements that are re-signified in this process.